The Muricidae (Gastropoda, Muricoidea) of the Miocene Central Paratethys Sea (Haustrinae, Muricinae, Ocenebrinae, Pagodulinae, Typhinae, Muricidae incertae sedis) - Harzhauser, Mathias; Landau, Bernard M.; Merle, Didier (Zootaxa, 2025)
We document 72 species of Haustrinae, Muricinae, Ocenebrinae, Pagodulinae, Typhinae and Muricidae incertae sedis from the Miocene of the Central Paratethys Sea. The subfamily Ocenebrinae is the most specious group within the Paratethyan Muricidae, comprising numerous new species. Muricinae, Muricidae incertae sedis and Typhinae display only low endemicity and comprise many paleogeographically widespread species. In contrast, Pagodulinae and Ocenebrinae are characterized by high endemicity and point to a Paratethyan hotspot of diversity of Ocenebrinae. The subfamily Haustrinae is recorded for the first time from the Miocene of the Circum-Mediterranean Region. The Paratethyan records suggest a Middle Miocene radiation of the deep water genus Timbellus which contains five species. Ocinebrinopsis nov. gen. is introduced as new genus. Ceratostoma? steiningeri sp. nov., Kestocenebra vermeiji sp. nov., Ocenebra scorpio sp. nov., Ocinebrinopsis gregaria sp. nov., Ocinebrinopsis aperta sp. nov., Ocinebrinopsis dominicii sp. nov., Ocinebrinopsis subnuda sp. nov., Ocinebrina bellissima sp. nov., Ocinebrina s.l. praescalaris sp. nov., Crassimurex (Eopaziella) zoltani sp. nov., Timbellus kovacsi sp. nov. and Timbellus weinmannae sp. nov. are described as new species. Ocenebra littoralis nov. nom. is proposed as new name for Murex (Ocinebrina) erinaceus sublaevis Schaffer, 1912 non Tate, 1888 and Pterynopsis guzhovi nov. nom. is introduced for Murex affinis Eichwald, 1830 non Gmelin, 1791. Ocenebra breitenbergeri sp. nov. is described as new species from the Middle Miocene of the Karaman Basin in Turkey.